Late effects on haemostasis after haematopoietic stem cell transplantation - Stussi, G.; Tsakiris, D. A. (Hämostaseologie, 2012)
Allogeneic and autologous hematopoietic stem cell transplantations are important therapeutic options for patients with hematologic disorders. Hemostatic complications are frequent after hematopoietic stem cell transplantation with a considerable morbidity and mortality. The incidence of bleedings and thrombosis is highest in the first few weeks after transplantation, but may also occur later. However, beyond the first year of transplantation only limited data are available. In longterm survivors the risk for premature atherosclerosis increases over time after allogeneic hematopoietic stem cell transplantation and it is higher than in the age-adjusted general population and in recipients of autologous transplantation.
Keywords: Haemostasis; venous thromboembolism; atherosclerosis; GvHD